Kelayakan Buku Suplemen Membaca Permulaan Berbasis Kearifan Lokal pada Kelas II Sekolah Dasar - Retno Suhartini; Kartono Kartono; Suparjan Suparjan; Hamdani Hamdani; Hery Kresnadi (FONDATIA, 2023)
Before actually moving on to the reading comprehension level, students must be proficient in their pre-reading skills. Hence, the researcher intended to create a supplementary book based on local wisdom for second graders to help their pre-reading skills proficiency. This research used a Research and Development (R&D) method with the adaption of the ADDIE model. 2 teachers, 31 students, and 6 expert review were chosen as the sample. Then, the data collection was conducted through interviews and questionnaires techniques. The result showed a “very good” response from students with a 90,5% percentage on the experiment and a “very good” response from teachers with a 96,66% percentage. These findings were supported and categorized as “very good” by the validation of linguistic experts with 92,5% percentage, 98,75% percentage for content experts, and 93,75% for design experts. In conclusion, this supplementary book is decent for pre-reading skill proficiency.